Pengaruh Pemberian Ekstrak Bawang Dayak terhadap Delayed Onset Muscle Soreness (DOMS) Ditinjau dari Kadar TNF-α: The Effect of Dayak Onion Extract on Delayed Onset Muscle Soreness (DOMS) in Terms of TNF-α Levels - Aulia Ramadhani; Hilda Carmitha Panjaitan; Fathurrahman Fathurrahman (UIMA Press, 2024)
Excessive physical activity can cause Delayed Onset Muscle Soreness (DOMS), associated with oxidative stress and inflammation. One inflammatory marker is Tumor Necrosis Factor Alpha (TNF-α). Eleutherine palmifolia (Dayak onion) contains flavonoids, saponins, and tannins with antioxidant and anti-inflammatory properties. This study aimed to analyze the effect of Dayak onion extract on TNF-α levels in a DOMS rat model induced by the Forced Swimming Test (FST). The study used a randomized pre- and post-test control Group design with five groups: K–, K+, and three treatment groups receiving 50, 100, and 200 mg/200 g BW doses for 21 days. The results showed a significant decrease in TNF-α levels, with the 200 mg/200 g BW dose (P3) exhibiting the greatest effect (91.36% compared to K–) and no significant difference compared to K+. In conclusion, a 200 mg/200 g BW dose per day was the most effective in reducing TNF-α levels associated with DOMS.